Obstacles to the Implementation of P5 on the Theme of Sustainable Lifestyle in the Green School Program at SMP Negeri 7 Banjarmasin - Siti Hapsah; Syaharuddin Syaharuddin; Rusmaniah Rusmaniah; Sovia Husni Rahmia; Sigit Triyono (The Innovation of Social Studies Journal, 2025)
The implementation (P5) of the sustainable lifestyle theme in the Merdeka Curriculum aims to increase students' awareness of the importance of caring for plants. This program also supports the Green School initiative which focuses on environmental conservation. SMP Negeri 7 Banjarmasin, students' awareness of the environment is still low. Less active in caring for plants, does not understand the importance of preserving the environment, and has limited knowledge about waste management. The integration of sustainable lifestyle themes in P5 is very important to support the success of the Green School program. However, the implementation of P5 faces various challenges that hinder the optimization of the implementation process. The solution is so that the implementation of P5 can run in accordance with the objectives of the Green School program. This research aims to identify the challenges that arise in implementing P5 with the theme of sustainable lifestyles as support for Green Schools. Using a qualitative approach and data collection methods through observation, interviews, and documentation, this research found obstacles, such as budget limitations, individual problems, and low student participation. Some proposed solutions include raising funds independently from students as well as increasing follow-up from teachers and students to encourage greater engagement.